ÙØ¹Ø§Ù„ÙŠØ© ØªØ¹Ù„ÙŠÙ… Ù‚ÙˆØ§Ø¹Ø¯ Ø§Ù„Ù†ØÙˆ Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© â€˜Ø§Ù„Ø®Ø±Ø§Ø¦Ø· Ø§Ù„Ø°Ù‡Ù†ÙŠØ©â€™ (Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø§Ù„ÙƒÙ…ÙŠØ© Ù„Ø·Ù„Ø¨Ø© Ø§Ù„ÙØµÙ„ Ø§Ù„Ø«Ø§Ù†ÙŠ ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø¯ÙŠÙ†ÙŠÙ‘Ø© â€˜Ø£Ù„Ø³ØªÙâ€™ ÙˆØ§ØªÙˆÙƒÙˆØ³ÙŠÙƒ Ø¨Ø§Ø³ÙˆØ±ÙˆØ§Ù† Ø¬Ø§ÙˆÙ‰ Ø§Ù„Ø´Ø±Ù‚ÙŠØ©) - Dihin Adhaniâ€™mah; M. Arif Setyabudi (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2021)
Nahwu science has been taught by many educational institutions in Indonesia, especially Madrasah Diniyah which applies the classical method (rote) in every lesson. However, sometimes the learning process at Madrasah Diniyah seems monotonous, boring and difficult for students to digest or understand. The results of the reliability test and correlation test: 1) The results of the Cronbach Alpha value reliability test between the Qowaid Nahwu sig learning effectiveness of (0.687> 0.6) and the Concept Mapping Learning Method of (0.707> 0.6) indicate no relationship. 2) The calculation of the correlation test that has been carried out with the Spearman correlation test from producing a value of 0.472 shows that H0 is accepted and HA is rejected, this indicates that there is no relationship between the variables of the effectiveness of Qowaid Nahwu learning and the Concept Mapping Learning Method. The spearman correlation coefficient value of -0.076 shows a negative correlation.